Application of biocharcoal aerogel sorbent for solid‐phase microextraction of polycyclic aromatic hydrocarbons in water samples. Issue 23 (13th October 2020) - Ji, Xiangping; Feng, Juanjuan; Li, Chunying; Han, Sen; Sun, Min; Feng, Jiaqing; Sun, Haili; Fan, Jing; Guo, Wenjuan
Abstract: A facile method was introduced for preparing a biocharcoal aerogel, which was derived from pomelo peel as the only raw material. The inner spongy layer of pomelo peel was freeze‐dried for maintaining three‐dimensional structure and then carbonized under high temperature and oxygen‐limited conditions. The morphological structure and graphitization degree of biocharcoal aerogel were characterized using a scanning electron microscope and Raman spectrum. After sifting and grinding, the biocharcoal aerogel as an adsorbent was coated onto the surface of stainless steel wires. Through placing the wires into a polyetheretherketone tube, the in‐tube solid‐phase microextraction device was obtained. Coupled with high‐performance liquid chromatography, it exhibited good extraction performance for polycyclic aromatic hydrocarbons, then an online analytical method was established with low limits of detection (0.005–0.050 ng/mL), wide linear ranges (0.017–15 ng/mL) with superior correlation coefficients higher than 0.9990, high enrichment factors (1128–3425), and acceptable intra‐ and inter‐day repeatabilities (relative standard deviations ≤ 6.7%, n = 3). The method was applied to detect polycyclic aromatic hydrocarbons in bottled water samples, environmental water samples, and soft drinks with satisfactory recoveries (83.3–120.9%). This research not only developed a new carbon aerogel but also evaluated its adsorption performance in sample preparation.